Taber's cyclopedic medical dictionary. - Taber, Clarence Wilbur 1870-; Thomas, Clayton L. 1921- (Philadelphia F.A. Davis, 1989)
Dictionary intended for nurses and other allied health personnel. Includes new terms reflecting changes and new topics in contemporary health care, e.g., AIDS, decision analysis, prescribing nurses, and clearinghouses serving consumer health needs. Biographical entries are also included. Entries give words, pronunciation, etymology, definition, subentries, abbreviation, synonyms, cross references, and colored illustrations. Miscellaneous appendixes. 1st ed., 1940; 15th ed., 1985.
"The nursing & allied health dictionary"--Cover and spine label.
Keywords: Medicine; Dictionaries, Medical